Research of organizational structure of retail business and educational institution by methods of statistical analysis - Aleksandr L. Bobkov; Igor V. Denisov; Oksana V. Kuchmaeva (Статистика и экономика, 2019)
The purpose of the study. The purpose of the research is to define a previously developed theoretical evolution model of an organizational structure, that is based on the hypothesis that the two types of organizational structures, consecutive and parallel, succeed each other, undergoing quality changes with the growth and development of organisations, though pertaining properties which determine the structure characteristics and provide a sufficient growth of organizations’ efficiency. Following the results of the authors’ previous research, it was hypothesized that the growth of an organization during a transition from one to the other type of organization structure follows either intensive or extensive pattern and is defined by the type of the transformation.Materials and methods. The study analyzed the retail trade sector, with isolated branches that distinguish this type of organizational structures, and educational institutions. The authors believe that organizations of similar types possess similar (consecutive and parallel) organizational structures. Groups of similar objects were identified by the cluster analysis used for grouping basic data. Following this, the results of cluster analysis were defined and key factors for patterns of organizational development were selected by the principal component analysis. Also, the Objectives Tree method was applied to gauge the effect of the types of educational services on the performance of private educational organizations and their structure. The research analyzed the data obtained from the database of commercial organizations of Czech Republic.Results. In general, the proposed model of the evolution of an organizational structure in retail business was redefined, and the outcomes of the conducted analysis allow defining the following:– when transitioning from the parallel to the consecutive organizational structure, the growth can be described as intensive, and while the consecutive model transitions to the parallel organizational structure the growth follows the extensive pattern;– development of retail business is defined by the three key factors: size of an organization, its performance efficiency and lifetime. The cluster analysis of educational organisations revealed seven clusters. After analysis of average values of variables, these clusters can be grouped in five. These outcomes led to the additional research with Objectives Tree, which showed that both small and large educational organisations employ their certain typical features of educational services. A similar pattern describes certain types of educational services in the organisations of different lifetime.Conclusion. The outcomes of the cluster analysis of commercial organisations of two sectors of Czech Republic and their further analysis confirmed the suggested hypothesis and matched corresponding theoretical evolution models of organizational structures, the results also showed intensive growth when transitioning from the parallel to the consecutive organizational structure and extensive growth when the transition changes from the consecutive to the parallel organizational structure. The alternating patterns of consecutive and parallel structures, as well as suggested gauging of the transition effectiveness will allow owners and management staff to efficiently maintain sustainable development of commercial organisations.